Effect of growth hormone treatment on diastolic function in patients who have developed growth hormone deficiency after definitive treatment of acromegaly. (February 2016) - Fazeli, Pouneh K.; Teoh, Jonathan G.; Lam, Eleanor L.; Gerweck, Anu V.; Wexler, Tamara L.; Teo, Eliza P.; Russell, Brian M.; Durst, Ronen; McCarty, David; Weiner, Rory B.; Picard, Michael H.; Klibanski, Anne; et al.
Abstract: Objective: Although growth hormone (GH) replacement is prescribed for patients with hypopituitarism due to many etiologies, it is not routinely prescribed for patients with GH deficiency (GHD) after cure of acromegaly (acroGHD). This study was designed to investigate the effect of GH replacement on cardiac parameters in acroGHD. Design: We prospectively evaluated for 12 months 23 patients with acroGHD: 15 subjects on GH replacement and eight subjects not on GH replacement. Main outcome measures included LV mass corrected for body surface area (LVM/BSA) and measures of diastolic dysfunction (E/A ratio and deceleration time), as assessed by echocardiography. Results: After 12 months of follow-up, there were no differences between the GH-treated group and the untreated group in LVM/BSA (GH: 74.4 ± 22.5 g/m 2 vs untreated: 72.9 ± 21.3 g/m 2, p = 0.89), E/A ratio (GH: 1.21 ± 0.39 vs untreated: 1.08 ± 0.39, p = 0.50) or deceleration time (GH: 224.5 ± 60.1 ms vs untreated: 260 ± 79.8 ms, p = 0.32). The overall degree of diastolic function was similar between the groups with 42.9% of untreated subjects and 50% of GH-treated subjects (p = 0.76) classified as having normal diastolic function at follow-up. Conclusions: There were no significant differences in LVM/BSA or parameters of diastolic function in patients with a history of acromegaly treated for GHD as compared to those who were untreated. These data are reassuring with respect to cardiovascular safety with GH use after treatment for acromegaly, although further longer term study is necessary to evaluate the safety and efficacy of GH treatment in this population. Highlights: Patients with GHD after cure from acromegaly are rarely treated with GH due to safety concerns. We followed 23 patients with a history of acromegaly and current GHD for 1 year. We measured echocardiographic parameters including diastolic function. At 1 year, overall degree of diastolic function was similar in patients treated with GH and those not treated with GH.